IMPLEMENTATION OF COGNITIVE BEHAVIORAL THERAPY (CBT) FOR THE ELDERLY IN REDUCING ANXIETY DUE TO LANDSLIDES IN MARGAMUKTI VILLAGE-BANDUNG REGENCY - Tukino Tukino (Indonesian Journal of Social Work, 2021)
This study aims to reveal the application of therapeutic communication in reducing anxiety experienced by elderly victims of landslides disaster in Margamukti Village, Pangalengan District, Bandung Regency. Specifically, this is to determine: 1) the physical condition of the elderly victims of landslides, 2) the psychological conditions of the elderly victims of landslides, 3) the social conditions of the elderly victims of landslides, 4) the application of therapeutic communication to reduce anxiety experienced by the elderly after landslides. This study uses a quantitative approach with a single subject design (SSD). The data collection technique is done through questionnaires, interviews, and observations. Analysis of research data using quantitative measurement techniques.The results showed that the application of therapeutic communication to respondent "Iy" resulted in a change for the better, namely a decrease in anxiety. During the measurement process, both the baseline phase A and the baseline phase B, and the measurement phase A2, from the aspect of the theurapeutic communication that was built between the researcher and the respondent "Iy", the process was quite meaningful, namely communication that built the respondent "Iy" growth towards psychosocial recovery.